Cross-Cultural Issues in the Translation of African Literature - Ogbeide-Ihama, Mojisola (Àgídìgbo: ABUAD Journal of the Humanities, 2015)
Language, culture and literature are inseparable elements in the process of translating literary texts. Thus translation is not just about transferring linguistic codes from one language to the other but a meeting point between the cultures involved. This meeting point allows us to identify and to understand the diversities of the cultures involved. Considering the linguistic and cultural diversities characterizing our world today, cultural translation makes it possible for us to discover the socio cultural context of the source text, thereby promoting mutual understanding and by consequence, global world peace. Culture is a dynamic phenomenon encompassing the totality of attitudes, behaviours, beliefs and world views. It is an integral part of every human society and all social groups are characterized by it. In other words, it is that "complex pattern of behaviour and material achievement which are produced, learned and shared by members of a community" (Ameh 2002: 165). In the conception of Peter Newmark, Culture is the way of life and its manifestations that are peculiar to a community that uses a particular language as its means of expression. (1988: 94) One crucial part of culture is language, as every culture has a language that best expresses it: there is no culture without a linguistic basis. Language is the means of expression and communication of a community. It serves to safeguard and to transmit their artistic and scientific acquisitions as well as their perceptions and world view. These world views in written form "literature" become accessible to all as a cultural product. By literature, we mean any. piece of writing that expresses human experience and feelings through imagination. It is a product of a culture and therefore of a people’s way of life and of the values or norms inherent in the society in which it is rooted. Therefore literature is the mirror to the values of a culture as it highlights the specifics and the socio cultural elements of a group of people.